Arise, awake, Africa! - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran at Kenyatta International Conference Centre Nairobi, Kenya, 28 Oct - 1 Nov 2007 in Africa
Title from title screen
V-Africa
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing